TRANSFERENCE OF METALS IN SOME NATIVE WETLAND SPECIES GROWING ON CRUDE OIL IMPACTED SOILS IN THE NIGER-DELTA, NIGERIA: IMPLICATIONS FOR PHYTOREMEDIATION POTENTIALS - Clement, Ogunkunle O; Olamide, Folarin O; Stephen, Olorunmiaye K; Mayank, Varun; Fatoba, Paul O (Journal of Agricultural Sciences (Belgrade), 2016)
In this study, wetland species growing naturally in the surrounding of two crude oil facilities were sampled and screened for phytoremediation potentials for zinc, lead, nickel, chromium and cadmium. Concentrations of metals in the root and shoot samples of the wetland species alongside the rhizosphere soil were determined. Metal accumulation in wetland species exceeded the permissible limits but still within phytotoxic thresholds except chromium. The use of bio-concentration factor and transfer factor to screen the wetland species for phytoremediation potentials identified six out of the eight studied species as multi-elemental phytostabilizers of metals in soil. In addition, five of the eight wetland species displayed potentials for phytoextraction of metal, though there was no multi-elemental phytoextractor among the wetland species. Paspalum vaginatum, Andropogon tectorum and Kyllinga squamata portend potential abilities to phytoextract nickel. In addition, Setaria longiseta and Pteridium aquilinum also showed strong potential to phytoextract lead and cadmium respectively from soil. This screening assessment is hoped to be useful in the applications of cost-effective green technology to remediate heavy metals in contaminated soil
Keywords: phytoremediation; wetland species; contaminated soil; trace metals; excluders; accumulators